2007
DOI: 10.1183/09031936.00006707
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-driven DNA damage mimics irradiation-related carcinogenesis pathways

Abstract: The epidemiological association between cancer and exposure to ambient air pollution particles (particles with a 50% cut-off aerodynamic diameter of 10 mm (PM10)) has been related to the ability of PM10 and its constituent nanoparticles (NPs) to cause reactive oxidative species (ROS)-driven DNA damage. However, there are no data on the molecular response to these genotoxic effects.In order to assess whether PM10, NP and ROS-driven DNA damage induce carcinogenesis pathways, A549 cells were treated with tert-but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
58
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(66 citation statements)
references
References 56 publications
7
58
0
1
Order By: Relevance
“…This result is consistent with previous studies by Lu et al and Mroz et al, which showed that nanoparticles and ROS can induce DNA damage, activate p53, and mimic irradiation-related carcinogenesis pathways. 88,89 Similarly, several studies reported that polyvinylpyrrolidone (PVP)-coated AgNPs induced p53 in the larval tissue of Drosophila melanogaster. 75,90 Taken together, the induction of the apoptotic pathway is indicated by the phosphorylation of p53 and ERK1/2.…”
mentioning
confidence: 99%
“…This result is consistent with previous studies by Lu et al and Mroz et al, which showed that nanoparticles and ROS can induce DNA damage, activate p53, and mimic irradiation-related carcinogenesis pathways. 88,89 Similarly, several studies reported that polyvinylpyrrolidone (PVP)-coated AgNPs induced p53 in the larval tissue of Drosophila melanogaster. 75,90 Taken together, the induction of the apoptotic pathway is indicated by the phosphorylation of p53 and ERK1/2.…”
mentioning
confidence: 99%
“…It has been shown that treating the A549 lung cancer cell line with nanoparticles induced DNA damage and G 2 /M arrest, and the induction of G 2 /M arrest was determined by the activation of P53 and the increased phosphorylation of the P53-binding protein, BRCA1, and γH 2 AX proteins. 35 Moreover, G 2 /M arrest was connected to a checkpoint kinase 1-associated signaling pathway, resulting in the inactivation of cyclin B1/Cdc2, and the nanoparticles could induce the phosphorylation of Cdc2 and Cdc25C prior to mitosis and cause the inactivation of cyclin B1. 36 Understanding the molecular mechanisms underlying the G 2 /M arrest caused by pGNRs@mSiO 2 -RGD nanoprobes requires further investigation.…”
mentioning
confidence: 99%
“…13,71 Apoptosis can be confirmed by abnormal reduction in the size of cells and DNA fragmentation, 13 and p53 is involved in the activation of apoptosis induced by DNA-damaging anticancer agents. [72][73][74] Previously, we have shown biologically synthesized AgNPs, GO, resveratrol-reduced GO, and plant extract-mediated rGO-AgNPs induce DNA fragmentation in various cancer cell lines, such as human breast cancer cells and ovarian cancer cells. 22,23,25 To examine DNA fragmentation, cells were treated with Cis (5 μM), rGO-AgNPs (1 μg/mL), or Cis plus rGO-AgNPs for 24 hours, and apoptotic signals were determined using TUNEL assay.…”
mentioning
confidence: 99%